THE INFLUENCE OF THE GUIDED INQUIRY LEARNING MODEL ON SCIENCE PROCESS SKILLS IN ECOSYSTEM MATERIAL - Sarah Agustin, Ayu; Kartini; Vidya Setyaningrum (AULADUNA: Jurnal Pendidikan Dasar Islam, 2024)
Abstract Science process skills were important for discovering knowledge concepts, but had not been fully trained at MIN 3 Pontianak. The guided inquiry learning model could train these skills. This study aimed to describe the effect of the guided inquiry learning model on science process skills in ecosystem material. The research method was quantitative with a true experimental pre-test and post-test control group design. The sample was taken randomly, with class VB as the experimental class and VA as the control class. The results showed that the guided inquiry learning model had no significant effect on science process skills inferentially, but descriptive analysis showed an increase in the average of these skills. Researchers need to conduct more in-depth evaluations and use more accurate instruments. This research can be the basis for improving science process skills, especially in the aspect of prediction to be higher.